2020
DOI: 10.1126/scisignal.aay6077
|View full text |Cite
|
Sign up to set email alerts
|

SMAR1 repression by pluripotency factors and consequent chemoresistance in breast cancer stem-like cells is reversed by aspirin

Abstract: The high abundance of drug efflux pumps in cancer stem cells (CSCs) contributes to chemotherapy resistance. The transcriptional regulator SMAR1 suppresses CSC expansion in colorectal cancer, and increased abundance of SMAR1 is associated with better prognosis. Here, we found in breast tumors that the expression of SMAR1 was decreased in CSCs through the cooperative interaction of the pluripotency factors Oct4 and Sox2 with the histone deacetylase HDAC1. Overexpressing SMAR1 sensitized CSCs to chemotherapy thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
(99 reference statements)
1
17
0
1
Order By: Relevance
“…Intriguingly, as mentioned above, asprin decreases the blood levels of several metabolites when cross checked with the human metabolome database. Our results are concordant with multiple reports showing that aspirin can suppress chemoresistance in various malignancies ( 27 32 ). A clinical trial is currently evaluating the efficacy of aspirin and tamoxifen in combination with doxorubicin as part of standard AC-T chemotherapy for treatment of high risk ER+ or ER- breast cancer (NCT04038489 clinicaltrials.gov).…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, as mentioned above, asprin decreases the blood levels of several metabolites when cross checked with the human metabolome database. Our results are concordant with multiple reports showing that aspirin can suppress chemoresistance in various malignancies ( 27 32 ). A clinical trial is currently evaluating the efficacy of aspirin and tamoxifen in combination with doxorubicin as part of standard AC-T chemotherapy for treatment of high risk ER+ or ER- breast cancer (NCT04038489 clinicaltrials.gov).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we showed that knockdown of HDAC2, but not other HDACs, rescue the inhibition of SMAR1 on ABCG2. Additionally, this SMAR1‐HDAC2 interaction is confirmed in breast cancer 15 . Notably, SMAR1 is shown to recruit HDAC5 to the promoter of β‐catenin in colorectal cancer 11 .…”
Section: Discussionmentioning
confidence: 72%
“…Consistently, a recent work shows that SMAR1 suppresses the stemness of breast cancer cells. 15 Therefore, further studies could be constructed to determine whether SMAR1-mediated inhibition on cancer cell stemness is a common phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations